Evaluation of the insolation model from LiDAR-derived topographical surface models / Nurhafiza Md Saad - Md Saad, Nurhafiza (2017)
The Sun illuminates the Earth and hence, provides the solar energy. Mankind and other forms of life use and benefits from this radiated energy in many ways towards sustainable planning and development of our nation. Earth's surface and objects differ in their types and materials. Thus, the incoming solar radiation or also known as insolation is expected to somehow change in regard to the initial solar energy due to the differing surface types and materials. Modelling the pattern of insolation of the Sun's rays as it interacts with the Earth's atmosphere, surface, and its objects is thus vital for many applications including in the context of green building technology concept. In this study, to reconstruct the surface models that represent the surface, high resolution airborne LiDAR datasets were used to produce the DTM and DSMs. The reliability of these models were verified accordingly. The derived products were further structured as TIN and topographic analysis as well as modelling was performed within ArcGIS environment. Models of irradiance were derived and distinguished based on the direct, diffuse and global irradiance. Then, the relationship of the response pattern with the topographical elements was determined and the results were discussed further in this study.